Dinâmica durante faltas e controle de conversores aplicados a sistemas fotovoltaicos de geração distribuída interligados à rede elétrica - Farias, Gustavo André Barbado (2019)
In recent years, it has become increasingly common to use Distributed Generation (DG) systems with renewable energy sources to compensate for both increased energy demand and the environmental impacts caused by the use of conventional sources. Within this context, one of the main used technologies is photovoltaic generation. With this, it becomes increasingly necessary to study strategies that guarantee a good performance of this type of system during electrical faults, and also a good post-fault recovery. This work deals with the dynamic characterization of DG grid-connected photovoltaic systems during faults. Then, simulations were made for the case of a 500-kW photovoltaic generation system. The first simulations had the purpose of demonstrating the effects of the operating limits of the converters on the dynamic behavior of the main variables of the system. Thus, the windup phenomenon is presented, which occurs when the current limits of the inverter are reached, directly affecting the final performance of the control meshes involved, causing undesired variation peaks and delays in the post-fault recovery. However, this work also presents an anti-windup strategy applied to the DC link voltage and reactive power control loops. These actions improved the system’s post-fault performance by reducing recovery time and eliminating large peaks in voltage, current and active power variations. The actions also avoided sudden variations in both the DC link voltage and the power generated by the photovoltaic array after the fault elimination. Thus, the anti-windup actions proved to be quite efficient in the dynamic improvement of the photovoltaic system during faults, regardless of the fault condition and the operating point of the system. In addition, a strategy for limiting the DC link during the fault was also proposed using an anti-windup analogue control scheme that acts on the duty cycle of the MPPT control loop. This strategy showed that it is possible to limit DC link voltage during the fault by reducing the photovoltaic array power generation and, in practice, could help to eliminate some protection problems involving the DC link voltage, such as the disconnection of the system from the main grid.